JOGJA LIBRARY CENTER TOUR: UPAYA MEWUJUDKAN LITERASI SEJARAH UNTUK MENINGKATKAN HISTORICAL THINKING SKILL - Wilis, Roro; Padang, Bonita; Kumalasari, Dyah (Jurnal Pendidikan Sejarah Indonesia, 2025)
This study aims to explore in depth the implementation of the Jogja Library Center Tour history learning model to actualize historical literacy and analyze its implications for improving historical thinking skills. This study uses a qualitative method with a case study approach at SMA Negeri 9 Yogyakarta. Data collection techniques were carried out comprehensively through interviews, observations, and document analysis. The sampling technique employed purposive sampling with several subjects, including the Vice Principal for Curriculum, history teachers, and student representatives from grades XI and XII at SMA Negeri 9 Yogyakarta. Data validity and reliability were obtained through data triangulation techniques and analyzed using the model promoted by Cresswell. The findings of this study indicate that the Jogja Library Center Tour is capable of representing an effort to improve the historical literacy of students at State Senior High School 9 Yogyakarta. In this context, the Jogja Library Center Tour model not only provides comprehensive understanding to students but also contributes to the success of the school's literacy program. The success of the Jogja Library Center Tour has implications for fostering historical thinking skills, such as chronological thinking, historical comprehension, historical analysis and interpretation, and historical research capabilities. The results of this study are beneficial as a reference for history teachers in the context of developing historical literacy and enhancing historical thinking skills to address challenges faced in school literacy programs in an enjoyable, interactive, and meaningful way.